2020
DOI: 10.1142/s1363919621500390
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Capability and Open Innovation and Its Impact on Performance in Smes: An Empirical Study in Chile

Abstract: The objective of this research is to analyse how risk-taking, commitment to learning, and innovation capability — in SMEs — can favour inbound and outbound open innovation practices, and if open innovation practices help their performance. To test the hypotheses simultaneously, partial least squares analysis (PLS-SEM) was used along with the empirical data obtained from 194 interviews with Chilean’s executives of manufacturing SMEs between 10 and 250 employees. The results obtained show that commitment to lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 117 publications
0
19
0
Order By: Relevance
“…Under the trend of economic globalization, innovation has become an important factor for enterprises to achieve success [1]. For new ventures in transition economies, innovation is not only an effective way to catch up with incumbents, but also a necessary way to cope with challenges in their early stages [2]. On the one hand, the introduction of the national policy of entrepreneurship and innovation in China has incubated a large number of new enterprises [3].…”
Section: Introductionmentioning
confidence: 99%
“…Under the trend of economic globalization, innovation has become an important factor for enterprises to achieve success [1]. For new ventures in transition economies, innovation is not only an effective way to catch up with incumbents, but also a necessary way to cope with challenges in their early stages [2]. On the one hand, the introduction of the national policy of entrepreneurship and innovation in China has incubated a large number of new enterprises [3].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this research defines innovation capability as the capability of innovating firms to integrate the firm’s core skills and resources to generate innovation. Carrasco-Carvajal & Garciá-Pérez-De-Lema (2020) pinpoint that innovation capability plays an enabler role in fostering open innovation [ 37 ]. They further illustrate that (1) innovation capabilities enable key stakeholders such as customers to interact with the innovations they develop, and (2) such a firm with knowledge-sharing capabilities would be better at sharing existing knowledge with its network partners [ 37 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Carrasco-Carvajal & Garciá-Pérez-De-Lema (2020) pinpoint that innovation capability plays an enabler role in fostering open innovation [ 37 ]. They further illustrate that (1) innovation capabilities enable key stakeholders such as customers to interact with the innovations they develop, and (2) such a firm with knowledge-sharing capabilities would be better at sharing existing knowledge with its network partners [ 37 ]. Therefore, this research implies that innovation capability has a positive relationship with the success of collaborative innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the contrary, there is a great deal of research on the impact of ICTs on innovation (Ebrahimi et al, 2018;Karakara & Osabuohien, 2020;Valdez-Juárez et al, 2018). In relation to innovation, considerable research in recent years has shown the existence of a direct and positive relationship between innovation and company performance (Carrasco-Carvajal & García-Pérez-de-Lema, 2021;Donbesuur et al, 2020;Roach et al, 2016;Zhu et al, 2019). Regarding CSR, the study of the effect of CSR on innovation has aroused the interest of many researchers.…”
Section: Introductionmentioning
confidence: 99%